OPTIMIZING EDUCATION MANAGEMENT TO IMPROVE LEARNING QUALITY - Sugianto, Endrik (Jurnal Konseling Pendidikan Islam, 2024)
This study aims to explore how optimizing educational management can improve the quality of learning through the literature review method. The research method used is a literature review, which involves the collection, analysis, and synthesis of information from various academic sources such as journals, books, research reports, and scholarly articles. The research process begins with the identification and selection of relevant literature, followed by a critical analysis of these sources to evaluate their quality and relevance. Subsequently, the collected information is synthesized to identify common themes and best practices in educational management that can be adopted to improve the quality of learning. The findings of this study indicate that strategic planning, effective organization, well-coordinated program implementation, and robust monitoring and evaluation systems are key components of effective educational management. Additionally, transformational school leadership, community and parental involvement, innovation and adaptation to technological advancements, student well-being, inclusive education, and continuous professional development for teachers also play crucial roles in enhancing the quality of education. These findings support existing theories and contemporary research in educational management, providing a comprehensive framework for improving educational quality through more effective management practices.